SHARQ MUTAFAKKIRLARINING KASBIY SHAKLLANISH MUAMMOSIGA DOIR MA’NAVIY-PSIXOLOGIK QARASHLARI - Yusupjonova, I.A. (SCIENCE and SOCIETY, 2024)
Analyzing the scientific literature on the studied problem, this study shows that the problem of students' professional choice and professional motivation is widely studied by Eastern thinkers. At the same time, general methodological and theoretical problems are theoretically analyzed related to the understanding and definition of professional identity.
Keywords: the process of professional development of psychology students; specific features of pedagogical communication; professional consciousness of a future psychologist; professional motivation and motivation; educational motivation